Interaction-tailored organization of large-area colloidal assemblies - Rizzato, Silvia; Primiceri, Elisabetta; Monteduro, Anna Grazia; Colombelli, Adriano; Leo, Angelo; Manera, Maria Grazia; Rella, Roberto; Maruccio, Giuseppe (Beilstein Journal of Nanotechnology, 2018)
Colloidal lithography is an innovative fabrication technique employing spherical, nanoscale crystals as a lithographic mask for the low cost realization of nanoscale patterning. The features of the resulting nanostructures are related to the particle size, deposition conditions and interactions involved. In this work, we studied the absorption of polystyrene spheres onto a substrate and discuss the effect of particle–substrate and particle–particle interactions on their organization. Depending on the nature and the strength of the interactions acting in the colloidal film formation, two different strategies were developed in order to control the number of particles on the surface and the interparticle distance, namely changing the salt concentration and absorption time in the particle solution. These approaches enabled the realization of large area (≈cm2) patterning of nanoscale holes (nanoholes) and nanoscale disks (nanodisks) of different sizes and materials.
Keywords: colloidal lithography; electrostatic interactions; large-area nanostructure patterning; localized surface plasmon resonance; spherical nanoparticles